The Annotated Statutes of Malaysia: companies commission of Malaysia Act 2001 (Act 614) - 2002 issue - Mohd. Sulaiman, Aiman @ Nariman (Malayan Law Journal Sdn Bhd, 2002)
With relevant Subsidiary Legislation: Companies Commission of Malaysia Act 2001 (Act 614)